PENGARUH PROMOSI, CITRA MEREK DAN LOKASI TERHADAP MINAT BELI KONSUMEN PADA TOKO IKA ANISA DI KABUPATEN SITUBONDO - Sariatik, Atika Puspita; Rachman, Riza; Fandiyanto, Randika; Ariyantiningsih, Febri (Growth, 2022)
The success of a store can be seen from the number of visitors. To face competition and maintain the continuity of the store, store owners need to plan the goals that will be achieved, so that they can determine what strategies will be used in dealing with existing competition to achieve consumer buying interest. The study explores the influence of promotion, brand image and location on consumer buying interest at the Ika Anisa store in Situbondo Regency. The population in this study were consumers who visited Ika Anisa's shop. This study used 97 respondents and used a simple random sampling method. Data collection was done by using a questionnaire. The data analysis technique used in this research is multiple linear regression analysis, t test, F test, dominant test and coefficient determination . Multiple linear regression analysis showed that Y = -3.790E-016 + 0.162X1 + 0.459X2 + 0.332X3 + e. The t-test for the hypothesis (H1) of the Promotion variable is 2.217 while the value in the 5% distribution ttable is 1.985 then tcount is 2.217 > 1.985 ttable, for the Brand Image variable is 5.440 while the value in the 5% distribution ttable is 1.985 then tcount is 5.440 > 1.985, for Location variable is 4,017 while the value at 5% distribution table is 1,985, so tcount is 4,017 > 1,985 ttable. F test results show that the hypothesis (H2) for the variables Promotion, Brand Image and Location have a simultaneous effect on Consumer Buying Interest at Ika Anisa Stores. The dominant test shows the hypothesis (H3) that the Brand Image variable has a dominant effect on Consumer Buying Interest at Ika Anisa Stores. The coefficient of determination (R2) shows a value of 0,530 from this result means that the independent variable nas a ontribution of 53% against the dependent variable that has a strong enough influence, and the remaining 47% is influenced by other variables.